EXPERIMENTAL ANALYSIS OF THE OUTPUT PERFORMANCE OF THE ABRASIVE EFFECT OF DUST ON PHOTOVOLTAIC CELLS - Benli, Hüseyin; Gürtürk, Mert; Ertürk, Neslihan Koçdemir (My University, 2020)
This article presents an evaluation of the power-voltage (P-V) and I-V characteristics of PV cells afterexposure to artificial dust spraying. The dusted cells and other clean cells have been to the tested,exposed to five different radiation ranges, and used a solar simulator. In the experiment, a solarsimulator analyzer was used to define the PVs' electrical performance, meantime a SandblastingCabinet and Atomic Force Microscope were used to inspect the properties abrasive of the dust on thecells. A significant reduction in both I-V and P-V properties was observed when dust accumulation onthe surface of photovoltaic solar cells was compared to the same parameters of the clean cells. Theaverage yield loss rate of solar cells exposed to dust spraying has decreased by 5-25% compared toclean cells, considering the inclination angle of the cells.
Keywords: Nanobilim ve Nanoteknoloji